APPROACHES TO INCREASE THE GASTRIC RESIDENCE TIME:FLOATING DRUG DELIVERY SYSTEMS- A REVIEW - SHASHANK , CHATURVEDI; Prabha, Kumari; Sunil , Singh; VIPIN KUMAR, AGRAWAL (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The purpose of writing this review was to compile recent literature on pharmaceutical approaches used in enhancing the Gastric residence time (GRT). Enhancing the GRT may explore new potentials of stomach as drug-absorbing organ. Several approaches are currently used including Floating Drug Delivery System (FDDS), swelling and expanding system, polymeric bioadhesive systems, modified-shape systems, high density system and other delayed gastric emptying devices. The drugs having absorption window in the upper part of Gastro Intestinal Tract (GIT) have enhanced bioavailability when formulated through these techniques. The recent technological development for enhancing GRT including the physiological and formulation variables affecting gastric retention, patented delivery systems, approaches to design single-unit and multiple-unit floating systems, and their classification and formulation aspects are covered in detail. In addition this review also summarizes the in vitro and in vivo studies to evaluate their performance and also their future potential